Pregnancy outcomes in women with anti-β2-glycoprotein I/human leukocyte antigen-DR autoantibodies receiving assisted reproductive technology: a prospective cohort study - Ono, Yosuke; Wada, Shinichiro; Kobayashi, Yuta; Ogi, Maki; Fukushi, Yoshiyuki; Tanimura, Kenji; Arase, Hisashi; Yoshino, Osamu; Yamada, Hideto (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to assess whether anti-β2-glycoprotein I (β2GPI)/human leukocyte antigen (HLA)-DR autoantibodies are associated with pregnancy outcomes in women with infertility receiving assisted reproductive technology (ART) in relation to antithrombotic therapies.MethodsIn this multicenter prospective cohort study, levels of anti-β2GPI/HLA-DR autoantibodies were measured in 194 women with infertility, who subsequently received embryo transfer (ET). The rates of clinical pregnancy, biochemical pregnancy loss, live birth, and miscarriage were assessed in relation to antibody positivity and antithrombotic treatments. The primary outcome was to evaluate how antithrombotic treatments were associated with pregnancy outcomes in women with anti-β2GPI/HLA-DR antibodies receiving ART. The treatment modality for the antibody-positive group was determined for each ET at the discretion of the attending physician.ResultsFinally, 30 women in the antibody-positive group and 123 in the antibody-negative group were analyzed. The prevalence of recurrent implantation failure in the antibody-positive group (40.0%, 12/30) was higher than that in the antibody-negative group (20.3%, 25/123; p = 0.024). The clinical pregnancy rate per ET tended to be lower in the antibody-positive group than in the antibody-negative group (30.4%, 21/69 vs 43.6%, 92/211; p=0.053), while the implantation rate per embryo was significantly lower in the antibody-positive group than in the antibody-negative group (26.3%, 21/80 vs 39.0%, 92/236; p=0.040). Among women in the antibody-positive group, low-dose aspirin (LDA), LDA plus unfractionated heparin (UFH), and non-LDA/non-UFH treatments were given in 30, 5, and 34 ET cases, respectively. The clinical pregnancy (42.9%, 15/35 ET vs. 17.6%, 6/34 ET; p = 0.044) and live birth (37.1%, 13/35 ET vs. 11.8%, 4/34 ET; p = 0.030) rates were higher in treated-group with LDA/UFH than non-LDA/non-UFH group. LDA/UFH treatment was independently associated with higher clinical pregnancy rates (adjusted odds ratio, 3.34; 95% confidence interval, 1.02–12.3; p = 0.047). Immunofluorescent staining showed coordinated expression of β2GPI and HLA-DR antigens on the epithelial cells of the eutopic endometrium in the antibody-positive group.ConclusionLDA/UFH treatment may be associated with higher clinical pregnancy and live-birth rates in women positive for anti-β2GPI/HLA-DR antibodies receiving ART.